Impact of Sugarcane Bagasse Ash (SCBA) and Cement to the Strength Improvement of Hemic Peat - Masri, Muhamad Hairi; Abu Talib, Mohd Khaidir (Journal of Sustainable Underground Exploration, 2023)
Peat soils are derived from organic deposition consisting of dead trees. Peat soils have low shear strength and cannot afford large loads. Various treatment methods are used to stabilize peat soils and most of them use cement as a main binder to increase the strength of peat soils. However, the use of large quantities of cement is not environment friendly due to the release of carbon dioxide (CO2) and wastage of energy consumption by the cement production industry. Therefore, the introduction of SCBA as a substitution binder for some cement dosage is good as well as reducing the degradation of dumping waste which is increasingly uncontrollable. The objective of this study is to identify the basic and physical properties of peat soil from Pontian, Johor. In addition, this study was also conducted to identify the impact of SCBA on peat soil stabilization with cement. There are 5 different mixtures for cement and SCBA which are C100, C95S5, C90S10, C85S15 and C80S20 used in this study. Sample C95S5 with mixtures 95% cement and 5% SCBA were the optimum samples for this study based on unconfined compression strength (UCS) tests. The C95S5 sample successfully achieved the maximum strength of the whole sample with a strength of 190 kN/m2, 209 kN/m2, and 219 kN/m2 recorded for wet curing periods of 7,14 and 28 days. Therefore, the use of SCBA materials in the stabilization of peat soils with cement and calcium chloride (CaCl2) is seen to have a positive effect in increasing the shear strength of Hemic peat soil samples.